2007
DOI: 10.1186/1743-8977-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between redox activity and chemical speciation of size-fractionated particulate matter

Abstract: The results of this work demonstrate the utility of the dithiothreitol assay for quantitatively assessing the redox potential of airborne particulate matter from a wide range of sources. Studies to characterize the redox activity of PM from various sources throughout the Los Angeles basin are currently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
155
5
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 48 publications
21
155
5
9
Order By: Relevance
“…Stronger associations during the cooler phase of study, despite similar PM 0.25 mass concentrations in cooler and warmer phases, further support the view that the greatest impacts on systemic responses may be attributable to nanoparticles not adequately represented by the present par ticle mass measurements as well as to unmea sured toxic air pollutants that increase near ground level in the winter. Our related experi mental work using particles collected in the LA air basin at the Southern California Particle Center suggests that this might include redox active and electrophilic organic components of traffic exhaust particles in the ultrafine range (Araujo et al 2008;Gong et al 2007;Li et al 2003;Ntziachristos et al 2007;Shinyashiki et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stronger associations during the cooler phase of study, despite similar PM 0.25 mass concentrations in cooler and warmer phases, further support the view that the greatest impacts on systemic responses may be attributable to nanoparticles not adequately represented by the present par ticle mass measurements as well as to unmea sured toxic air pollutants that increase near ground level in the winter. Our related experi mental work using particles collected in the LA air basin at the Southern California Particle Center suggests that this might include redox active and electrophilic organic components of traffic exhaust particles in the ultrafine range (Araujo et al 2008;Gong et al 2007;Li et al 2003;Ntziachristos et al 2007;Shinyashiki et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms involving oxidative stress and inflammation have been proposed to explain these associations (Mills et al 2007) (Figure 1). In addition, a growing toxicol ogy literature suggests that ultrafine particles (UFP), < 0.1 µm in diameter, may have greater potential to induce oxidative stress and inflammation than larger particles that domi nate PM 2.5 and PM 10 mass (Ntziachristos et al 2007). This is likely because compared with larger particles, UFP have a higher air way deposition efficiency, magnitudes higher particle number (PN) concentration and sur face area, and higher concentrations of organic components shown to induce oxidative stress responses (Li et al 2003).…”
mentioning
confidence: 99%
“…Ultrafine particles carry more redox-active components than larger particles, which are more spatially homogenous. 7,31,32 Based in large part on experimental evidence, it has been hypothesized that particles from vehicular exhaust, especially in the ultrafine range, can trigger oxidative stress. When antioxidant responses are then overwhelmed, airway inflammation may follow, leading to increasing asthma symptoms in susceptible children.…”
Section: Overview Of Findings and Implicationsmentioning
confidence: 99%
“…Previous studies reported strong associations between the PAH content of atmospheric PM samples and DTT (Cho et al, 2005;Ntziachristos et al, 2007b). Biswas et al (2009) measured the chemical composition and redox activity of particles from a variety of diesel engines, and found that there is a strong association between water soluble organic carbon (WSOC), organic acids, and DTT.…”
Section: Pm Volatility and Its Impact On Public Exposure And Healthmentioning
confidence: 99%